Les médias : source de victimisation - Parent, Georges-André (Criminologie, 1990)
With the advent of the Bill of Rights, making the offender less accessible, journalists are falling back more than ever on the victim to feed their daily tales of victimization.The author analyses the various forms this source of victimization takes; for some victims, they are generally crimes that are spectacular and violent, and are often perpetrated against the most susceptible and vulnerable victims.Each type of media (radio, dailies, weeklies, television) represents a particular way of adding to the suffering of the victim, and each has its way of “exploiting” the victim. The victim becomes a tool of the media, both commercially and ideologically, often with the connivance of the police, who also uses the victim for its purposes.The victim is portrayed in stereotype, according to the type of victimization reported and the offender implicated, creating a guilty or innocent victim, and literally depriving him of his own account of his victimization to make it an object of curiosity that sells well.Finally, the author analyzes how the police and the media, by interaction, can exploit the victim under the pretext of prevention or crime control and even through certain phenomena such as the reporting of crime waves promoting fear of crime. The article concludes that the media should have more respect for victims of crime.